Ninety years of change on a low wooded island, Great Barrier Reef. Issue 6 (19th June 2019) - Hamylton, S. M.; McLean, R.; Lowe, M.; Adnan, F. A. F.
Abstract : We assess 90 years of change on a Low Wooded Island (Low Isles, Great Barrier Reef), employing drones and topographic profiling to accurately survey ramparts, mangroves, the reef flat and the sand cay. A comparison with maps from the 1928–1929 Great Barrier Reef Expedition revealed the redistribution of an outer rampart and inward movement of shingle ridges. Remarkable lateral expansion of the mangrove woodland some 400 m has occurred as carbonate sand deposition has increased reef flat elevation, obscuring coral microatolls. The sand cay has stayed relatively constant in size, moving approximately 44 m in a northeasterly direction and rotating slightly. We conclude that the existing configuration of landforms probably represents an equilibrium with local biophysical conditions, including sea level, wave dynamics, vegetation growth, storms and cyclones. The variable nature of ramparts and the presence of a trough that prevents the continuous spread of mangroves across a uniformly flat colonization surface precludes the interpretation of landform changes with respect to a geomorphic evolutionary sequence. Moreover, longer-term implications of environmental change for these landforms can only be evaluated once the specific nature of the local carbonate budget, including the relative contribution of corals, foraminifera and Halimeda has been elucidated.